Understanding the formation mechanism of oolong tea characteristic non-volatile chemical constitutes during manufacturing processes by using integrated widely-targeted metabolome and DIA proteome analysis. (25th April 2020) - Wu, Liangyu; Huang, Xujian; Liu, Shengrui; Liu, Jianghong; Guo, Yuqiong; Sun, Yun; Lin, Jinke; Guo, Yaling; Wei, Shu
Highlights: Proteomic and metabolomic data were integrated for oolong tea flavor study. Totally 782 metabolites and 7245 proteins in processed tea leaves were found. 46 metabolic biomarkers exhibited significant changes over the processing steps. An association between some proteins and their metabolic products was revealed. Both enzymatic and non-enzymatic reactions affect flavor chemical formation. Abstract: To interpret the enzymatic modulation of the dynamic changes of small molecules in tea leaves during oolong tea manufacturing process, the metabolomic and proteomic studies were performed using processed leaf samples collected at the different manufacturing stages and non-processed fresh leaves as control. As a result, a total of 782 metabolites were identified, of which 46, as the biomarkers, were significantly changed over the manufacturing process. Totally 7245 proteins were qualitatively and quantitatively determined. The abundance of multiple enzymes including phenylalanine ammonia lyase, peroxidase and polyphenol oxidase was positively associated with the dynamic changes of their corresponding catalytic products. The overall protein-metabolite association analysis showed that over the enzymatic-catalyzed process production of some non-volatile components, such like carbohydrates, amino acids and flavonoids, were related with the abundance of those responsible proteins in different extents and potentially contributed to the comprehensive flavor of oolong tea.